Peroxide-assisted microwave activation of pyrolysis char for adsorption of dyes from wastewater. (September 2016) - Nair, Vaishakh; Vinu, R.
Graphical abstract: Highlights: Biochar from Prosopis juliflora was activated using H2 O2 -microwave treatment. Effects of H2 O2 soaking time and microwave power on biochar properties were studied. Optimal conditions correspond to 24 h soaking in H2 O2 and 600 W microwave power. Adsorption of RBBR and Methylene Blue dyes on activated biochars was investigated. Dye adsorption obeys pseudo second order kinetics and Langmuir–Freundlich isotherm. Abstract: In this study, mesoporous activated biochar with high surface area and controlled pore size was prepared from char obtained as a by-product of pyrolysis of Prosopis juliflora biomass. The activation was carried out by a simple process that involved H2 O2 treatment followed by microwave pyrolysis. H2 O2 impregnation time and microwave power were optimized to obtain biochar with high specific surface area and high adsorption capacity for commercial dyes such as Remazol Brilliant Blue and Methylene Blue. Adsorption parameters such as initial pH of the dye solution and adsorbent dosage were also optimized. Pore size distribution, surface morphology and elemental composition of activated biochar were thoroughly characterized. H2 O2 impregnation time of 24 h and microwave power of 600 W produced nanostructured biochar with narrow and deep pores of 357 m 2 g −1 specific surface area. Langmuir and Langmuir–Freundlich isotherms described the adsorption equilibrium, while pseudo second order model described the kinetics of adsorption.